한국전쟁기 경북 성주군의 부역자 처벌과 피학살자유족회 활동 - 이윤갑 (한국학논집, 2012)
이 논문은 한국전쟁기 경상북도 성주지역에서 경찰이 전쟁부역자를 처벌한 사건과 1960년 4월 혁명 직후 일어난 피학살자유족회 활동을 연구하였다. 북한 인민군은 1950년 8월 3일부터 9월 24일까지 성주군을 점령하고 지배하였다. 이 기간 동안 인민군은 인민위원회 지배체제를 수립하고, 경찰과 공무원을 비롯한 우익인사들을 처형하고, 전쟁 물자 운반에 필요한 노동력을 동원하고, 식량과 의복 등의 군수물자를 징발하였다. 또한 전사자가 증가함에 따라 부족한 병력을 충원하는 의용군을 모집하였다. 이와 같은 인민군의 전쟁동원정책에 참여한 자는 자의에 의한 것이든 타의에 의해 강제된 것이든 전부 부역자로 규정되었고, 처벌대상이 되었다. 유엔군이 성주를 수복하자 경찰은 인민위원회와 치안대에 가입하여 활동하였던 자들을 검거해 부역자로 처벌하였다. 경찰의 부역자 처벌은 두 단계로 이루어졌다. 첫 단계는 수복 직후 검거한 부역자 가운데 48명을 선별해 집단학살하였다. 이 학살은 조속히 치안을 확보하겠다는 정치적 의도에서 이루어진 적법 절차를 거치지 않은 불법적 학살로써 심각한 국가범죄였다. 둘째 단계는 경찰이 검거한 부역자를 심문해 검찰로 송치하여 재판에 회부하는 것이었다. 이러한 처벌은 수복 직후부터 1951년 초반까지 계속되었다. 당시 경찰의 심문기록이 남아있는 자는 총 160명이다. 재판에 회부된 부역자 가운데 10년 이상 중형을 선고받은 소수를 제외한 나머지 대다수는 1950년 12월 대통령 특사령에 의해 감형 또는 형 면제 처분을 받고 석방되었다. 1960년 4월혁명으로 이승만정권이 무너지자 수복 직후 경찰에 의해 집단 학살된 부역자의 유족들은 집단학살의 진상을 규명하고, 책임자를 처벌하고, 희생자의 명예를 회복하기 위해 피학살자유족회 운동을 전개하였다. 그러나 이 운동은 1961년 쿠데타로 군사정권이 등장하면서 탄압을 받고 해체되었다. 한국전쟁기 부역자 처벌은 성주 사회에 심각한 분열과 내상을 남겼고, 그 치유는 현재까지도 미완의 과제로 남아있다. This paper analyzed the cases of collaborators punishment by the police in Seongju, Gyeongsangbuk-do during Korean War and surviving family activities happened shortly after the revolution in April 1960. North Korea People’s Army dominated and occupied Seongju from August 3 to September 24, 1950. During this period, the People’s Army established People’s Committee governance systems. They executed police officers and officials, including rightists, mobilized the labor needed to transport war materials, and commandeered military supplies, including food and clothing. In addition, they recruited militias to reinforce troops as increasing number of dead soldiers. All collaborators were subject to punishment since they participated in the war mobilization policies whether by their will or by imposing the regulations. When UN troops restored Seongju, the police arrested those who joined the People’s Committee and charged the collaborators with war criminals. The police punished the collaborators with a two step process. The first step was genocide of 48 collaborators right after restoration. The massacre was a serious crime and illegal slaughter politically motivated to ensure a national security. The second step was to go to trial for the prosecution’s questioning of collaborators arrested by the police. These penalties continued until the early 1951 after the restoration. People remaining on the police interrogation records were 160. The majority of collaborators were commuted or released by special presidential pardon in December, 1950, except for ones sentenced to more than 10 years. As soon as Rhee Syngman regime collapsed in April 1960 revolution, surviving families by genocide after restoration started a campaign to investigate and reveal the truth of genocide, punish those responsible, and restore the honor of the victims. However, this campaign was dismantled during a coup in 1961 under the military dictatorship of Park Chung-hee. After collaborators punishment during Korean War, people were divided and internally injured and there has been the work of healing divisions in Seongju until today. KCI Citation Count: 2